Dialogando com professores: o celular como analisador da relação professor/mídia/aluno - Ribeiro, Diana Montenegro (2017)
In the context of relevant influence of new technologies, it is important to consider the effects of the teacher / student / media relation at school. Bruno (2013) indicates that the new technologies affect not only the limits of what is lived in the public and in the private, as it brings us to a different way of producing subjectivity. Children and adolescents who were already born in a technological age attend schools that are still following disciplinary standards of the time of their expansion (SIBILIA, 2012b). With the prohibition or restriction of cell phone use in the classroom, especially after the emergence of smartphones, teachers expect students to increase their productivity (concentration, learning, results). Following Foucauld's thinking that school is an example of a disciplinary society's and taking into account so many changes that have already occurred in disciplinary codes and the new forms of control that media help shape, how the school is dealing with this issue contemporary? The present master's research, through an intervention research carried out from an extension course, sought to analyze the positions of the teachers of a public school, located in the city of Fortaleza, about the media-education relationship, having as analyzer the cellular. From observations made in the classroom, talk wheels, fanzine and video workshops, we problematize power relations and surveillance in the school today, as well as the judicialization of this institution occurs from the use of legal practices to prohibit the use of the cell phone in the classroom. The possibility of using the cell phone as a pedagogical tool was also discussed. In addition, through a video constructed by the teachers participating in the research, we perceive the opening of space for other voices, a polyphonic space without consensus, but consciously heterogeneous as the school space should be.